High-shell-forming fire-resistant heat-insulating low-smoke halogen-free flame-retardant polyolefin cable material and preparation method thereof

By optimizing the components of the cable material, the synergy of EVA, polylactic acid, nanocellulose crystals, ammonium polyphosphate, silicone flame retardant and inorganic filler are solved, and the problem of crystallization water reverse osmosis of the fire-resistant cable material during high temperature burning is improved, and the safety and flame retardant performance of the cable are improved.

CN119752017AInactive Publication Date: 2025-04-04SHANGHAI FANGZHIDE NEW MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411725342.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing fireproof cable materials may release crystallized water when burned at high temperatures, resulting in damage to the integrity of the fireproof barrier structure and reducing the safety performance of the cable.

Method used

Optimized cable components, including EVA, polylactic acid, nanocellulose crystals, ammonium polyphosphate, silicone flame retardants and inorganic fillers, are used to ensure that crystallization water does not easily reverse osmosis through the fire barrier during high temperature burning.

Benefits of technology

It effectively maintains the structural integrity of the fire barrier, improves the safety performance of the cable, ensures high safety in extreme environments such as fire, and meets the flame retardant requirements of low smoke and halogen-free.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005159068740000051
    Figure BDA0005159068740000051
  • Figure BDA0005159068740000052
    Figure BDA0005159068740000052
  • Figure BDA0005159068740000061
    Figure BDA0005159068740000061
Patent Text Reader

Abstract

The invention relates to a high-shell-forming fire-resistant heat-insulation low-smoke halogen-free flame-retardant polyolefin cable material and a preparation method thereof, and the high-shell-forming fire-resistant heat-insulation low-smoke halogen-free flame-retardant polyolefin cable material comprises the following components in parts by weight: 80-100 parts of EVA (Ethylene-Vinyl Acetate); 45 to 60 parts of polylactic acid; 10 to 20 parts of nano cellulose crystal; 5 to 10 parts of ammonium polyphosphate; 10 to 15 parts of an organic silicon flame retardant; 30-40 parts of an inorganic filler; the ammonium polyphosphate is mid-polymerized ammonium polyphosphate, and the polymerization degree of the ammonium polyphosphate is 45-50. The preparation method of the high-shell-forming fire-resistant heat-insulation low-smoke halogen-free flame-retardant polyolefin cable material comprises the following preparation steps: preparing modified polylactic acid; s3, preparing modified EVA (Ethylene Vinyl Acetate); mixing and preparing the modified polylactic acid and the modified EVA; and post-processing. The components of the cable material are optimized, particularly ammonium polyphosphate is adopted as an effective flame-retardant component, modified EVA is adopted as a matrix and is combined with modified polylactic acid, crystal water of the cable material is not prone to reverse osmosis through a fireproof barrier when the cable material is burnt at a high temperature, and therefore the structural integrity of the fireproof barrier is effectively maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of fireproof cables, and in particular to a high-shell fire-resistant, heat-insulating, low-smoke, halogen-free, flame-retardant polyolefin cable material and a preparation method thereof. Background Art

[0002] With the vigorous development of social economy, the application scope of cables is becoming more and more extensive, and the demand is also showing a rapid growth trend. Cable materials, as key materials for insulation and sheathing of wires and cables, are directly related to the safety and stability of cables in terms of quality and performance. However, at the same time, the number of electrical fire accidents is also rising year by year, posing a serious threat to people's lives and property safety. Therefore, the current state has put forward more stringent requirements on the fire resistance of cables to ensure that cables can maintain a certain fire resistance time when a fire occurs and reduce fire losses.

[0003] Fireproof cables, as a cable product with excellent fireproof performance, are receiving increasing attention for their research and development and application. Fireproof cables are made of special cable materials that not only have excellent flame retardant properties, but also can maintain stable electrical performance in high temperature environments.

[0004] At present, high-shell fireproof cable materials are widely used in the electrical industry. Through chemical reactions, they form a solid protective shell on the outer layer of the cable, effectively isolating the conductor inside the cable from the external environment. When the cable is exposed to fire or other high-temperature effects, this protective shell can quickly solidify to form a hard fire barrier to prevent the spread of flames and the conduction of heat into the cable. This feature enables high-shell cable materials to maintain the integrity of the cable in a fire, extend the working time of the cable in a fire, and provide valuable power support for emergency rescue and personnel evacuation.

[0005] The fire-proof cable material in the related technology is added with porcelain powder, which can be transformed into a hard and dense ceramic body when exposed to open flames or high temperature environments, thereby blocking the fire source. In order to achieve a certain flame retardant effect, a large amount of aluminum hydroxide and magnesium hydroxide mixture is also required as a flame retardant. However, when burned at high temperatures, these substances may release crystalline water, which will adhere to the surface of the ceramic body and penetrate into the interior, causing tiny cracks or gaps inside the ceramic body, thereby weakening the structural integrity of the ceramic body, reducing its overall mechanical properties and insulation properties, making it easier for flames or heat to penetrate into the cable, affecting the safety performance of the cable. Summary of the invention

[0006] In order to solve the problem in the related art that crystalline water may be released during high-temperature burning, resulting in damage to the integrity of the fire barrier structure, thereby reducing the safety performance of the cable, the present application provides a high-shell fire-resistant, heat-insulating, low-smoke, halogen-free, flame-retardant polyolefin cable material and a preparation method thereof.

[0007] In the first aspect, the present application provides a high shell fire-resistant, heat-insulating, low-smoke, halogen-free, flame-retardant polyolefin cable material using the following technical solutions: A high shell fire-resistant, heat-insulating, low-smoke, halogen-free and flame-retardant polyolefin cable material, comprising the following components in parts by weight: 80-100 parts of EVA; Polylactic acid 45-60 parts; 10-20 parts of nanocellulose crystals; Ammonium polyphosphate 5-10 parts; 10-15 parts of silicone flame retardant; 30-40 parts of inorganic filler; The ammonium polyphosphate is a medium-polymer ammonium polyphosphate with a polymerization degree of 45-50.

[0008] By adopting the above technical solution: optimizing the components of the cable material so that the crystal water is not easy to reverse permeate through the fire barrier when burned at high temperature, the structural integrity of the fire barrier is effectively maintained and the safety performance of the cable is improved.

[0009] Preferably, the inorganic filler is one or more of zinc borate, white carbon black, porcelain powder, and aluminum hydroxide.

[0010] By adopting the above technical solution: the selection of inorganic fillers has an important influence on the performance of cable materials. Zinc borate has good flame retardant properties and can absorb a large amount of heat when the cable material burns, reducing the burning speed of the material, thereby playing a flame retardant role. At the same time, zinc borate can also chemically react with other components in the cable material to form stable compounds, thereby improving the thermal stability of the cable material; White carbon black has a high specific surface area and strong adsorption properties, which can enhance the physical and mechanical properties of cable materials. It can also interact with organic polymers in cable materials, improve the interfacial bonding force of cable materials, and enhance the overall performance of cable materials. Secondly, ceramic powder can form a ceramic structure at high temperatures, which has excellent thermal insulation and thermal shock resistance. Adding ceramic powder as an inorganic filler to cable materials can effectively improve the fire resistance and thermal insulation properties of cables and protect the safety of cables in extreme environments such as fires. As an inorganic flame retardant, aluminum hydroxide can release a large amount of water vapor when the cable material burns, diluting the oxygen concentration in the air, thereby reducing the burning speed. At the same time, aluminum hydroxide can also absorb the heat generated by the burning of the cable material, further reducing the burning temperature of the material.

[0011] Preferably, the cable material further comprises 3-6 parts of a silane coupling agent.

[0012] Preferably, the silane coupling agent is one or more of vinyltriethoxysilane and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.

[0013] By adopting the above technical solution: the silane coupling agent plays a bridge role in the cable material, which can improve the compatibility between the inorganic filler and the organic polymer and enhance the interfacial bonding force between them. In this way, when the cable material is subjected to external force, the inorganic filler and the organic polymer are not easy to separate or fall off, thereby improving the overall mechanical properties and stability of the cable material; Secondly, vinyl triethoxysilane and β-(3,4-epoxycyclohexyl)ethyl trimethoxysilane are representatives of silane coupling agents, which have excellent reactivity and stability. They can chemically bond with functional groups such as hydroxyl and carboxyl in cable materials to form a stable chemical structure, further improving the thermal and chemical stability of cable materials.

[0014] In addition, the addition of silane coupling agent can also help improve the processing performance of cable materials. During the process of melt blending and melt co-refining, silane coupling agent can promote the uniform dispersion and mixing of various components of cable materials, reduce the viscosity of cable materials, improve fluidity, and make the preparation process of cable materials smoother and more efficient.

[0015] In the second aspect, the present application provides a method for preparing a high shell fire-resistant, heat-insulating, low-smoke, halogen-free, flame-retardant polyolefin cable material, which adopts the following technical solution: A method for preparing a high shell fire-resistant, heat-insulating, low-smoke, halogen-free, flame-retardant polyolefin cable material, the preparation steps are as follows: S1, mixing nanocellulose crystals and ammonium polyphosphate and adding solvent I to grind, and after grinding sufficiently, drying to obtain a mixture A; S2, adding polylactic acid to mixture A, melt blending, to obtain mixture B, for standby use; S3, mixing EVA, silane coupling agent and inorganic filler, melting and refining to obtain mixture C, and setting aside; S4, adding mixture B, mixture C, and the organosilicon flame retardant into a torque rheometer, heating, and reacting to obtain mixture D; S5. Add mixture D to solution II, filter to obtain a crude product, wash and dry to obtain.

[0016] By adopting the above technical solution: the method has clear steps and is easy to operate, and can effectively prepare cable materials with excellent performance.

[0017] Preferably, the solvent I in S1 is an aqueous solution of ethanol (ethanol: water = 85%: 15%).

[0018] By adopting the above technical solution: the refinement and uniformity of the components can be further promoted. After sufficient grinding, a drying step is performed to obtain a mixture A, which provides a uniform raw material basis for subsequent steps.

[0019] Preferably, the solvent II in S5 is DMF.

[0020] By adopting the above technical solution, impurities and unreacted components in the cable material can be effectively removed to obtain a pure cable material product.

[0021] Preferably, in S4, the heating temperature is 160-180° C., the reaction time is 55-60 min, and the rotor speed is 45-60 rpm.

[0022] By adopting the above technical solution: in this step, chemical reaction and physical mixing occur between the components to form a cable material with excellent performance. The control of heating temperature and reaction time is crucial to the performance of the cable material. By optimizing these process parameters, ideal cable material performance can be obtained.

[0023] In summary, the present application includes at least one of the following beneficial technical effects: 1. This application optimizes the components of the cable material, especially uses medium-poly ammonium polyphosphate as an effective flame retardant component, uses modified EVA as a matrix combined with modified polylactic acid, and the crystal water of the cable material is not easy to reverse-permeate through the fire barrier when burned at high temperature, thereby effectively maintaining the structural integrity of the fire barrier. At the same time, the synergistic effect of the silicone flame retardant and the inorganic filler further improves the flame retardant performance of the cable. This cable material can maintain a high degree of safety in extreme environments such as fire; 2. This application adopts a low-smoke, halogen-free flame retardant formula, which produces less smoke when burning and does not contain harmful substances such as halogens, meeting environmental protection requirements. This helps to reduce the impact of smoke on personnel evacuation and rescue work when a fire occurs, while reducing the potential harm of the cable to the environment during use. DETAILED DESCRIPTION

[0024] The present application is further described in detail below in conjunction with the examples. Except for the special instructions below, the raw materials used in the present application are all common commercially available materials.

[0025] EVA is purchased from DuPont EVA40L-03 in the United States Polylactic acid is purchased from France NaturePlast PLI 003 Nanocellulose crystals are purchased from Wuhan Langbowan TEMPO modified cellulose nanocrystals Performance testing The tensile strength (MPa) and elongation at break (%) of the samples were tested according to GB / T1040.3; The flame retardant properties of the samples were tested according to GB / T24093 and characterized by oxygen index (%); The smoke density of the sample was tested according to GB / T 8323-2008 and characterized by light transmittance (%); Toxicity index of the samples tested according to GB / T 17650; The volume resistivity (Ω·cm) of the samples was tested according to GB / T 1410. Example

[0026] Example 1 A high shell fire-resistant heat-insulating low-smoke halogen-free flame-retardant polyolefin cable material, the components and the corresponding amounts of which are shown in the following table, and is prepared by the following preparation method: S1, mixing nanocellulose crystals and ammonium polyphosphate, adding 85% ethanol solution, and grinding in a ball mill. After sufficient grinding, drying, to obtain a mixture A; S2, adding polylactic acid to mixture A, melt blending at 220°C to obtain mixture B, which is set aside; S3, EVA, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane and inorganic filler are mixed, melted and co-refined at 190° C. to obtain a mixture C, which is set aside; S4, adding mixture B, mixture C and the organosilicon flame retardant into the torque rheometer, with the rotor speed of 50 rpm, heating at 160° C. for 55 min to obtain mixture D; S5. Add the mixture D into DMF, filter to obtain a crude product, wash with methanol and dry in vacuum to obtain the product.

[0027] Table: Components and their weights in Example 1 (kg) Among them, the usage of inorganic fillers is shown in the following table: Table: Usage of inorganic filler in Example 1 Inorganic fillers Zinc borate, white carbon black, aluminum hydroxide Comparative Example 1 A high shell fire-resistant, heat-insulating, low-smoke, halogen-free and flame-retardant polyolefin cable material, which is different from Example 1 in that the ammonium polyphosphate is high-poly ammonium polyphosphate with a degree of polymerization of 60.

[0028] Comparative Example 2 A high shell fire-resistant, heat-insulating, low-smoke, halogen-free and flame-retardant polyolefin cable material, which is different from Example 1 in that the ammonium polyphosphate is an oligomeric ammonium polyphosphate with a degree of polymerization of 20.

[0029] The samples prepared in Example 1 and Comparative Examples 1-2 were selected and tested for performance according to the above test standards. The results were averaged. The test results are shown in the following table: Table: Performance test results of Example 1 and Comparative Examples 1-2 As can be seen from the table above, the cable material sample prepared in Example 1 has excellent performance in all aspects. When subjected to high temperature to simulate combustion, its volume resistivity still reaches 3.9*10 15 Ω·cm, which indicates that the crystal water of the cable material is not easy to reverse permeate through the fire barrier when burned at high temperature, and can effectively maintain the structural integrity of the fire barrier; Analyze the possible reasons: Nanocellulose crystals have a large number of hydroxyl functional groups, which can form hydrogen bonds with polar groups in ammonium polyphosphate molecules. Through the interaction of hydrogen bonds, nanocellulose crystals can be wrapped around ammonium polyphosphate to form a tight complex. This complex not only improves the mechanical strength of the cable material, but also helps to form a dense fire barrier during the combustion process to prevent flame and heat penetration; At the same time, during the melt blending process, the nanocellulose crystal-ammonium polyphosphate composite interacts with polylactic acid. The molten state of polylactic acid enables it to penetrate into the voids of the composite and form a more tightly interwoven structure with the nanocellulose crystals and ammonium polyphosphate. This structure not only enhances the thermal stability of the cable material, but also helps to improve the flame retardant properties of the cable material. β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, as a coupling agent, can react with EVA and inorganic fillers in a molten state. The addition of inorganic fillers increases the volume and mechanical strength of the cable material, and also interacts with other components in the cable material through its special physical and chemical properties. The inorganic fillers can form physical crosslinking points with nanocellulose crystals, ammonium polyphosphate and polylactic acid, further improving the overall performance of the cable material. In addition, the inorganic fillers can absorb heat and dilute combustible gases during the combustion process, thereby enhancing the flame retardant properties of the cable material. Furthermore, the functional groups in the modified polylactic acid interact with the modified EVA, forming a stable chemical bond connection between the two and constructing a cross-linked network. This cross-linked network significantly improves the thermal stability and mechanical strength of the cable material, allowing the cable material to maintain good performance at high temperatures. During the combustion process, the organosilicon flame retardant can decompose to produce silicon oxides, which can form a dense protective film on the surface of the cable material. This protective film can isolate the contact between oxygen and flame, preventing the combustion from proceeding. At the same time, silicon oxide can also absorb heat and dilute the combustible gas, further reducing the combustion rate. Therefore, when the cable material is eroded by flames, under high temperature conditions, the nanocellulose crystal-ammonium polyphosphate complex will form a first layer of dense fire barrier, and the silicone flame retardant will form a second layer of protective film. Even if the aluminum hydroxide in the inorganic filler releases a large amount of crystalline water, it will not easily reverse osmosis through the two layers of fire barriers, thus ensuring the safety of the cable.

[0030] As for Comparative Examples 1 and 2, under high temperature conditions, the volume resistivity decreased by an order of magnitude, while the tensile strength and elongation at break in Comparative Example 1 decreased significantly compared with Example 1. This may be due to the poor compatibility of high-polymerization ammonium polyphosphate with other components, requiring a longer melt blending time or a higher temperature to fully mix. This inhomogeneity may make it easy for the cable material to form local thermal weaknesses at high temperatures, thereby reducing the volume resistivity of the cable material; In addition, high-polymerization ammonium polyphosphate may be difficult to fully disperse into the cable material matrix due to its long molecular chain and poor fluidity in the molten state, which also affects the overall performance of the cable material.

[0031] The low-polymerization degree ammonium polyphosphate used in Comparative Example 2 may be relatively weak in flame retardancy and cannot form an effective fire barrier, which also leads to a decrease in volume resistivity. In addition, the low-polymerization degree ammonium polyphosphate may also have certain compatibility issues during the melt blending process, but the impact may be smaller than that of the high-polymerization degree ammonium polyphosphate.

[0032] Embodiment 2-8 A high shell fire-resistant, heat-insulating, low-smoke, halogen-free and flame-retardant polyolefin cable material, which is different from Example 1 in that the amounts of the components are different.

[0033] Table: Components and their weights in Examples 2-8 (kg) The samples prepared in Examples 2-8 were selected and performance tested according to the above test standards. The results were averaged. The test results are shown in the following table: Table: Performance test results of Examples 2-8 From the above table, we can see that the change in the amount of each component has different degrees of influence on the various properties of the cable material. As the amount of polylactic acid increases, the transmittance increases, but the oxygen index decreases. In addition, as the amount of the silicone flame retardant increases, the oxygen index reaches 55%, while the light transmittance is 65%, which shows a slight decrease. In Example 8, although the strength is higher, the toxicity index has a greater increase compared with Example 1. It is worth mentioning that in Examples 2-8, the volume resistivity under high temperature conditions has almost no significant change from that under normal temperature conditions, and the performance is good.

[0034] Examples 9-14 A high shell fire-resistant, heat-insulating, low-smoke, halogen-free and flame-retardant polyolefin cable material, which is different from Example 1 in that the use of inorganic fillers is different.

[0035] Table: Usage of inorganic fillers in Examples 9-14 The samples prepared in Examples 9-14 were selected and performance tested according to the above test standards. The results were averaged. The test results are shown in the following table: Table: Performance test results of Examples 9-14 It can be seen from the above table that different inorganic fillers have different degrees of influence on the performance of cable materials. In Example 9 and Example 12, the volume resistivity (450°C) is 9.1*10 14 Ω·cm and 9.6*10 14 Ω·cm, which is one order of magnitude different from the volume resistivity at 20°C. At the same time, the oxygen index in Example 9 reaches a new high of 56%, while the tensile strength and elongation at break have a slight downward trend; In Example 10 and Example 11, the volume resistivity (450°C) is 1.2*10 15 Ω·cm and 1.4*10 15 Ω·cm, which is quite different from that in Example 1. In Examples 13-14, the volume resistivity (450°C) and the oxygen index decrease slightly.

[0036] As an inorganic filler, aluminum hydroxide has a significant effect on improving the flame retardant properties of cable materials. It can decompose and absorb heat at high temperatures, releasing water vapor to dilute combustible gases, thereby achieving an oxygen index of up to 56% in Example 9, significantly improving the flame retardant effect. However, it also has its limitations. The increase in aluminum hydroxide may affect the continuity and fluidity of the cable material, resulting in a slight decrease in tensile strength and elongation at break. At the same time, different inorganic fillers have their own unique performance characteristics. White carbon black can improve the hardness and wear resistance of cable materials, zinc borate is known for its excellent flame retardant and smoke suppression properties, and vitrified powder can form a ceramic protective layer at high temperature, significantly enhancing the fire resistance and heat insulation properties of cable materials. The combined use of these fillers may produce a synergistic effect and bring multiple performance improvements to cable materials. However, it is worth noting that the mixed use of multiple fillers may also lead to a decrease in certain performance indicators due to the interaction between them. In addition, these inorganic fillers also have a significant effect on the volume resistivity of the cable material. In Examples 10 and 11, fillers such as white carbon black and zinc borate interact with other components in the cable material to form a more stable charge transfer channel, which significantly improves the volume resistivity (450°C) compared with Example 1. However, in Examples 13 and 14, the combined use of multiple fillers may increase the complexity of charge transfer, resulting in a slight decrease in volume resistivity. Furthermore, we can observe from Examples 9 and 12 that, although the volume resistivity at high temperature remains at a high level, it is lower than the volume resistivity at 20°C. This may be because the dispersion and existence state of the inorganic filler in the cable material affects the transfer and accumulation of charges, further proving the significant effect of the inorganic filler on the volume resistivity of the cable material.

[0037] Examples 15-16 A high shell fire-resistant, heat-insulating, low-smoke, halogen-free and flame-retardant polyolefin cable material, which is different from Example 1 in that a different silane coupling agent is used.

[0038] Table: Usage of silane coupling agent in Examples 15-16 The samples prepared in Examples 15-16 were selected and performance tested according to the above test standards. The results were averaged. The test results are shown in the following table: Table: Performance test results of Examples 15-16 From the above table, it can be seen that the samples prepared by Example 15 and Example 16 performed worse than Example 1 in the test result of toxicity index, and the strength of Example 15 was also slightly lacking; The change in the toxicity index may be related to the toxicity of the silane coupling agent itself or its decomposition products in the cable material. Vinyl triethoxysilane may release harmful substances during processing or use, causing the toxicity index to rise. In addition, vinyl triethoxysilane may react chemically with other components in the cable material to produce new harmful substances, which is also a possible reason for the change in the toxicity index.

[0039] Comparative Example 3 A high shell fire-resistant, heat-insulating, low-smoke, halogen-free and flame-retardant polyolefin cable material, which is different from Example 1 in that the solvent I in S1 is pure ethanol.

[0040] Comparative Example 4 A high shell fire-resistant, heat-insulating, low-smoke, halogen-free and flame-retardant polyolefin cable material, which is different from Example 1 in that the solvent I in S1 is a 50% ethanol solution.

[0041] Comparative Example 5 A high shell fire-resistant, heat-insulating, low-smoke, halogen-free and flame-retardant polyolefin cable material, which is different from Example 1 in that the solvent II in S5 is acetone.

[0042] The samples prepared in Comparative Examples 3-5 were selected and performance tested according to the above test standards. The results were averaged. The test results are shown in the following table: Table: Performance test results of comparative examples 3-5 As can be seen from the table above, the tensile strength and elongation at break in Comparative Example 3 are slightly improved, and the volume resistivity (450°C) is 1.6*10 15 Ω·cm, there is a significant decrease. In Comparative Example 4, the volume resistivity at both 20°C and 450°C is reduced to varying degrees. As for Comparative Example 5, its oxygen index is 32%, which is a larger decrease than the other two comparative examples, but the volume resistivity (450°C) does not decrease but increases.

[0043] In Example 1, the use of 85% ethanol solution may help to fully dissolve and disperse the nanocellulose crystals and ammonium polyphosphate. When the ethanol concentration is increased to pure ethanol (Comparative Example 3), the properties of the solvent may change, resulting in changes in the solubility and dispersion state of the solute in the solvent. Pure ethanol may lead to more complete solvent volatilization, but during the volatilization process, it may cause the rearrangement of the nanocellulose crystals and ammonium polyphosphate, which may lead to the instability of the performance of the cable material at high temperatures (such as 450°C), which is manifested as a downward trend in volume resistivity; The 50% ethanol aqueous solution contains more water than the 85% ethanol solution, which may cause the solvent evaporation rate to slow down in the subsequent drying step, affecting the preparation process of the cable material and indirectly affecting the performance of the cable material. In addition, DMF as a solvent in Comparative Example 5 may help to evenly disperse the flame retardant in the cable material, thereby exerting its flame retardant effect. However, when acetone is used instead of DMF, the dispersion of the flame retardant may be affected, resulting in uneven distribution in the cable material, reducing the flame retardant effect, and then manifested as a significant decrease in the oxygen index.

[0044] The above are all modifications without creative contribution or solutions that obviously constitute technical inspiration that can be made to the present embodiment as needed by technical personnel in this field after reading this specification, but they should be protected by patent law as long as they are within the scope of the claims of this application.

Claims

1. A high shell fire-resistant heat-insulating low-smoke halogen-free flame-retardant polyolefin cable material, characterized in that: The invention comprises the following components in parts by weight: 80-100 parts of EVA; Polylactic acid 45-60 parts; 10-20 parts of nanocellulose crystals; Ammonium polyphosphate 5-10 parts; 10-15 parts of silicone flame retardant; 30-40 parts of inorganic filler; The ammonium polyphosphate is a medium-polymer ammonium polyphosphate with a polymerization degree of 45-50.

2. The high shell fire-resistant, heat-insulating, low-smoke, halogen-free, flame-retardant polyolefin cable material according to claim 1, characterized in that: The inorganic filler is one or more of zinc borate, white carbon black, porcelain powder and aluminum hydroxide.

3. The high shell fire-resistant, heat-insulating, low-smoke, halogen-free and flame-retardant polyolefin cable material according to claim 1, characterized in that: The cable material also includes 3-6 parts of a silane coupling agent.

4. The high shell fire-resistant, heat-insulating, low-smoke, halogen-free, flame-retardant polyolefin cable material according to claim 3, characterized in that: The silane coupling agent is one or more of vinyl triethoxysilane and β-(3,4-epoxycyclohexyl)ethyl trimethoxysilane.

5. The method for preparing the high shell fire-resistant, heat-insulating, low-smoke, halogen-free and flame-retardant polyolefin cable material according to any one of claims 1 to 4, characterized in that: The following preparation steps were adopted: S1, mixing nanocellulose crystals and ammonium polyphosphate and adding solvent I to grind, and after grinding sufficiently, drying to obtain a mixture A; S2, adding polylactic acid to mixture A, melt blending, to obtain mixture B, for standby use; S3, mixing EVA, silane coupling agent and inorganic filler, melting and refining to obtain mixture C, and setting aside; S4, adding mixture B, mixture C, and the organosilicon flame retardant into a torque rheometer, heating, and reacting to obtain mixture D; S5. Add mixture D to solution II, filter to obtain a crude product, wash and dry to obtain.

6. The method for preparing the high shell fire-resistant, heat-insulating, low-smoke, halogen-free and flame-retardant polyolefin cable material according to claim 5, characterized in that: The solvent I in S1 is an aqueous solution of ethanol (ethanol: water = 85%: 15%).

7. The method for preparing the high shell fire-resistant, heat-insulating, low-smoke, halogen-free and flame-retardant polyolefin cable material according to claim 5, characterized in that: The solvent II in S5 is DMF.

8. The method for preparing the high shell fire-resistant, heat-insulating, low-smoke, halogen-free and flame-retardant polyolefin cable material according to claim 5, characterized in that: In the S4, the heating temperature is 160-180° C., the reaction time is 55-60 min, and the rotor speed is 45-60 rpm.

Citation Information

Patent Citations

  • Porcelainized polyolefin composite material and preparation method thereof

    CN104497404A

  • Flame-retardant high polymer material based on compounding of phosphorus containing char-forming agents and hypophosphite / phosphonate

    CN106496729A

  • Fireproof expanding low-smoke halogen-free flame-retardant sheath material and preparation method thereof

    CN106750855A

  • Cross-linked low-smoke halogen-free flame-retardant polyolefin cable material and preparation method thereof

    CN111662497A

  • High-flame-retardant high-shell-forming low-smoke halogen-free flame-retardant oxygen barrier layer cable material

    CN111690202A